Pengaruh Pemberian Seduhan Teh Hijau (Camellia Sinensis) Terhadap Kadar Glukosa Darah dan Malondialdehide (MDA) - Ma’rifat Istiqa Mukty (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Oxidative stress is a condition where there is an imbalance between oxidants and antioxidants in the body which can trigger psychological stress. Oxidative stress can be reduced by consuming exogenous antioxidants (antioxidants from outside), where green tea is thought to be able to reduce oxidative stress. The aim of this study was to examine the effect of steeping green tea on blood glucose and Malondialdehyde (MDA) levels in male Wistar Strain white rats exposed to psychological stress. The design used in this research was Randomized Post Test Only Group Design. There were 5 groups of mice; 2 are a normal control group and a stress control group, and 3 treatment groups. Previously, the mice were given psychological stress 1 x 24 hours in the form of disturbed sleep patterns, so that the experimental animals experienced oxidative stress, then green tea was given to the treatment group with a single dose of 3.6 ml/head in the 1st hour in the group. treatment 1, 6th hour in treatment group 2, and 24th hour in treatment group 3. Statistical analysis used the Manova test. Based on statistical analysis, it shows that there was a decrease in blood glucose and Malondialdehyde (MDA) levels in all treatment groups given exposure to psychological stress and steeping green tea. A single dose of green tea brewing in experimental animals experiencing oxidative stress was proven to be able to neutralize oxidative stress in the 1st hour after administration of green tea brewing and the antioxidant activity still lasted up to 24 hours.